Enhancing financiers’ accountability for the social and environmental impacts of biofuels - Gelder, J.W. van; Kouwenhoven, D. (Center for International Forestry Research, 2011)
This report summarises 20 case studies on investments in the production of biofuel and the feedstocks used for biofuel (palm oil, soybeans, sugarcane and jatropha) in forest-rich countries in Africa, Asia and Latin America. The investments were financed by private entrepreneurs, public financing and private financial institutions. A large number of private financial institutions such as banks, asset managers and pension funds were investing, most of which are located outside the country where the investment took place. Dozens of public financial institutions—many of which are foreign—play a significant role. Since the availability of finance is a crucial precondition for the further growth of the biofuel sector, these actors could play an important role in leveraging more sustainability in the sector. However, our findings suggest that most investors are not yet effectively addressing key environmental and social sustainability challenges, either because they lack sustainability policies or because their policies are of insufficient quality. Realising the potential influence of investors on minimising the negative social and environmental costs associated with feedstock expansion and biofuel production requires improved dissemination of high-quality governance instruments. Whilst private and public investors could develop and adopt better policies voluntarily, we also discuss regulatory options available to governments in production and consumption countries. These options could motivate or assist private financial institutions in developing and applying sound, responsible financing policies.